Liver fibrosis and MAFLD: the exploration of multi-drug combination therapy strategies - Dong, Qingfu; Bao, Haolin; Wang, Jiangang; Shi, Wujiang; Zou, Xinlei; Sheng, Jialin; Gao, Jianjun; Guan, Canghai; Xia, Haoming; Li, Jinglin; Kang, Pengcheng; Xu, Yi; et al. (Frontiers in Medicine, 2023)
In recent years, the prevalence of metabolic-associated fatty liver disease (MAFLD) has reached pandemic proportions as a leading cause of liver fibrosis worldwide. However, the stage of liver fibrosis is associated with an increased risk of severe liver-related and cardiovascular events and is the strongest predictor of mortality in MAFLD patients. More and more people believe that MAFLD is a multifactorial disease and that multiple pathways are involved in promoting the progression of liver fibrosis. Numerous drug targets and drugs have been explored for various anti-fibrosis pathways. The treatment of single medicines is brutal to obtain satisfactory results, so the strategies of multi-drug combination therapies have attracted more and more attention. In this review, we discuss the mechanism of MAFLD-related liver fibrosis and its regression, summarize the current intervention and treatment methods for this disease, and focus on the analysis of drug combination strategies for MAFLD and its subsequent liver fibrosis in recent years to explore safer and more effective multi-drug combination therapy strategies.